KARAKTERISTIK MORFOMETRIK DAN MERISTIK IKAN LAIS DANAU (Ompok hypophthalmus Bleeker, 1846) DI SUNGAI TAPUNG DAN SUNGAI SIAK - Putri, Riri Anggraini; Elvyra, Roza; ', Yusfiati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This research is one of study about morphometric-meristic of lais danau fish (Ompokhypophthalmus) in two different habitats, Tapung river and Siak river. The purpose of this research is to determine the difference between morphometric and meristic of male lais danau fish and female lais danau fish in Tapung river and Siak river. This research was conducted on January-March 2014. As many as 60 fish (consisting of 30 males and 30 females) were collected every month for each loacation. The data were analyzed using Microsoft Excel and SPSS Version 16. Morphometric characters of lais danau fish in Siak river, are smaller than the males and females of lais danau fish in Tapung river. The growth status of lais danau fish for each location of the research are positive allometric, negative allometric, and isometric. T-test showed that morphometric between male lais danau fish and female lais danau fish for each location of the research were significant different. Meristic of male lais danau fish and female lais danau fish for each location of the research were not significant different.